Once after a full moon: acute type A aortic dissection and lunar phases. (27th August 2021) - Bjursten, Henrik; Oudin Åström, Daniel; Nozohoor, Shahab; Ahmad, Khalil; Tang, Mariann; Bjurbom, Markus; Hansson, Emma C; Jeppsson, Anders; Joost Holdflod Møller, Christian; Jormalainen, Miko; Juvonen, Tatu; Mennander, Ari; et al.
Abstract: : OBJECTIVES: Acute type A aortic dissection (ATAAD) is a rare but severe condition, routinely treated with emergent cardiac surgery. Many surgeons have the notion that patients with ATAAD tend to come in clusters, but no studies have examined these observations. This investigation was undertaken to study the potential association between the lunar cycle and the incidence of ATAAD. METHODS: We collected information on 2995 patients who underwent ATAAD surgery at centres from the Nordic Consortium for Acute Type A Aortic Dissection collaboration. We cross-referenced the time of surgery with lunar phase using a case-crossover design with 2 different definitions of full moon (>99% illumination and the 7-day full moon period). RESULTS: The period when the moon was illuminated the most (99% definition) did not show any significant increase in incidence for ATAAD surgery. However, when the full moon period was compared with all other moon phases, it yielded a relative risk of 1.08 [95% confidence interval (CI) 1.00–1.17, P = 0.057] and, compared to waxing moon, only the relative risk was 1.11 (95% CI 1.01–1.23, P = 0.027). The peak incidence came 4–6 days after the moon was fully illuminated. CONCLUSIONS: This study found an overrepresentation of surgery for ATAAD during the full moon phase. The explanation for this is not known, but we speculate that sleep deprivation during full moon leads to a temporary increase in blood pressure, which in turn could trigger rupture of the aortic wall. While this finding is interesting, it needs to be corroborated and the clinical implications are debateable. Abstract : The impact our nearest celestial body has on our ecosystem, society and humans has been studied and debated for at least 20 000 years [1] when humans first started to record the lunar cycle.